2024
DOI: 10.3390/ijms25021338
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Mediterranean Diet and Lifestyle Intervention on Lipoprotein Subclass Profiles among Metabolic Syndrome Patients: Findings of a Randomized Controlled Trial

Beatriz Candás-Estébanez,
Bárbara Fernández-Cidón,
Emili Corbella
et al.

Abstract: Metabolic syndrome (MetS) is associated with alterations of lipoprotein structure and function that can be characterized with advanced lipoprotein testing (ADLT). The effect of the Mediterranean diet (MedDiet) and weight loss on the lipoprotein subclass profile has been scarcely studied. Within the PREDIMED-Plus randomized controlled trial, a sub-study conducted at Bellvitge Hospital recruiting center evaluated the effects of a weight loss program based on an energy-reduced MedDiet (er-MedDiet) and physical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…Nutrients 2024, 16, x FOR PEER REVIEW 3 of 17 compared to MD recommendations without caloric restrictions, with the conclusion that the MD combined with caloric restrictions plus increased physical activity reduced plasma triglycerides and increased HDL-cholesterol particles, and also reduced weight, indicating beneficial changes against cardiovascular disease [18]. Furthermore, a review suggests that MD adherence can be considered the first step in the treatment of MetS [26].…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…Nutrients 2024, 16, x FOR PEER REVIEW 3 of 17 compared to MD recommendations without caloric restrictions, with the conclusion that the MD combined with caloric restrictions plus increased physical activity reduced plasma triglycerides and increased HDL-cholesterol particles, and also reduced weight, indicating beneficial changes against cardiovascular disease [18]. Furthermore, a review suggests that MD adherence can be considered the first step in the treatment of MetS [26].…”
Section: Study Populationmentioning
confidence: 99%
“…A meta-analysis of 4 randomized controlled trials and 32 cohort studies found that higher adherence to the MD was associated with improved cardiovascular health outcomes, including significant reductions in rates of cardiac ischemia, cerebrovascular ischemia, and total heart diseases [ 8 ]. Likewise, numerous studies have confirmed the protective effects of the MD against various chronic diseases, including type 2 diabetes mellitus [ 9 , 10 , 11 ], cardiovascular diseases [ 12 , 13 ], cognitive impairment [ 14 ], certain types of cancer [ 15 ], aging disorders [ 16 , 17 ], and metabolic syndrome (MetS) [ 18 ]. Likewise, greater adherence to the MD was linked to a 23% reduction in the risk of all-cause mortality [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely established that patients with metabolic syndrome (MetS), characterized by elevated triglyceride (TG) levels, decreased levels of HDL-C, and increased levels of small dense LDL particles (sd-LDL), exhibit alterations in lipoprotein structure and function. A study led by Dr. Pintó investigated the impact of the Mediterranean diet (MedDiet) and weight loss on lipoprotein subclasses within the PREDIMED-Plus trial, utilizing advanced lipoprotein testing (ADLT) based on nuclear magnetic resonance spectrometry (NMR) [ 1 ]. Specifically, MetS patients were assigned to a group consisting of an energy-reduced MedDiet (er-MedDiet) with physical activity (PA) promotion or a control group.…”
mentioning
confidence: 99%